Integrating psychology in a prisoner's reformation program - Saplala, J. Enrique G. (Quezon City Psychological Association of the Philippines, 2011)
"Most men who go through incarceration experience behavioral changes in different ways. Initial experiences include an imbalance between their cognition and affect. This paper looked into the development of prison reformation programs in several countries and an evaluation of Skwelahang Sikolohiya, a sixteen-year-old prison reformation program based in the Philippine national penitentiary."
Keywords: Prisoner reformation -- Philippines; Psychology modules -- Philippines; Evidence-based reformation program -- Philippines